Choice is Suffering: A Focused Information Criterion for Model Selection - Behl, Peter; Dette, Holger; Frondel, Manuel; Tauchmann, Harald (Economic Modelling, 2012)
In contrast to conventional measures, the Focused Information Criterion (FIC) allows the purpose-specific selection of models, thereby reflecting the idea that one kind of model might be appropriate for inferences on a parameter of interest, but not for another. Ever since its invention, the FIC has been increasingly applied in the realm of statistics, but this concept appears to be virtually unknown in the economic literature. Using a straightforward analytical example, this paper provides for a didactic illustration of the FIC and demonstrates its usefulness in economic applications. © 2011 Elsevier B.
WiSo-Import:2015-03-26:4660
Keywords: Akaike Information Criterion; Schwarz Information Criterion; Translog cost function